The "Crista Ovale": A Reliable Anatomical Landmark in Transorbital Endoscopic Approaches to the Middle Cranial Fossa. Issue 3 (12th March 2023) - Yanez-Siller, Juan C.; Noiphithak, Raywat; Martinez-Perez, Rafael; Dallan, Iacopo; Moe, Kris S.; Revuelta Barbero, Juan M.; Howe, Edmund; Prevedello, Daniel M.; Carrau, Ricardo L.
Abstract : BACKGROUND: Transorbital endoscopic approaches (TOEAs) have emerged as adjunct and alternatives for accessing the middle cranial fossa (MCF). Nuances of the skull base anatomy from a ventral transorbital endoscopic viewpoint remain to be fully described. OBJECTIVE: To assess the anatomy of the "crista ovale" (COv), described transcranially as the midsubtemporal ridge (MSR), from a ventral transorbital perspective and evaluate its role as a landmark in TOEA to the MCF. METHODS: Lateral TOEAs to the MCF were performed in 20 adult cadaveric heads (40 sides). The presence of the COv/MSR was evaluated under endoscopic visualization. Anatomic relationships between COv/MSR and surrounding structures were assessed. The presence of COv/MSR was also examined in 30 cadaveric head computed tomography (CT) scans (60 sides). RESULTS: The COv/MSR was identified in 98% (39/40) of sides at the MCF, as 1 of 4 major configurations. The COv/MSR was found anterolateral to the foramen ovale and foramen spinosum (mean distance: 9.2 ± SD 2.4 mm and 12.3 ± SD 2.6 mm, respectively) directly anterior or anteromedial to the petrous apex (mean distance: 26.2 ± SD 2.6 mm) and at a mean 47.6 ± SD 4.7 mm from the approach's surgical portal. It was recognized in 95% (57/60) of CT scans. CONCLUSION: The COv/MSR can be readily identified during TOEA to the MCF and on CT. It serves as a reliable landmark to localize the foramen ovale, foramen spinosum, and petrous apex. Further studies may confirm its surgical significance in transorbital endoscopic procedures.